India's Turn in Climate Policy: Assessing the Interplay of Domestic and International Policy Change - Joachim Betz (German Institute of Global and Area Studies (GIGA), 2012)
India has long been regarded as a deal-breaker in international climate negotiations; it was at the summit in Copenhagen that India first abandoned its old strategic line and made a commitment to reduce carbon emissions voluntarily. This shift was accompanied by a proliferation of domestic initiatives to save energy, to develop regenerative energies, etc. Traditional IR approaches remain insufficient to explain this policy shift - which is the aim of this paper - insofar as they fail to adequately take into account the fact that climate policies have to confront two audiences: a domestic and an international one, each presenting different tactical necessities for official reaction. On the international front, we argue that globally, India intended to be perceived as a responsible actor, one deserving of a greater say in global governance matters. On the domestic level, shrinking national energy reserves and mounting import dependence made the co-benefit of energy saving in reducing greenhouse gas emissions evident. The shift was made easier because important business associations aligned with a more eco-friendly development perspective and because the reduction commitments made by the Indian government on an international stage did not demand very stringent domestic emission reductions.
Keywords: 300; India; climate policies; greenhouse gas emissions; international climate summits; strategy shift; energy saving; Klimaveränderung; Umweltpolitik; Treibhausgas; Energiesparen; Indien